2017
DOI: 10.1007/s12594-017-0564-4
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Petrography of the Nagar Parkar Igneous Complex, Southeastern Sindh, Pakistan: The Kharsar Body

Abstract: Kharsar hill is one of many granitic plutons comprising the Nagar Parkar igneous complex. The eastern part of the hill is occupied by grey-pink granite (earlier) and the western part by pink granite (later). They are composed of perthite, quartz, and plagioclase, with minor opaque oxide, biotite, titanite, local amphibole, and secondary chlorite, epidote, leucoxene/titanite. The pink granite is characterized by the presence of mafic clots. Both the granitoids are intruded by microgranite/aplite, and porphyriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…The interpreted source rocks for the Jumara Dome sediments are exposed in the Aravalli Craton and Nagar Parkar Massif terrain in east and northeast, and north and northwest directions, respectively (Jan, Agheem, Laghari, & Anjum, 2017). The synthesis of paleocurrent data collected for this study (n = 37, vector mean = 351.694; n = 30, vector mean = 74.995) indicates the contribution from both these terrains (Figure 8).…”
Section: Trace Elementsmentioning
confidence: 79%
“…The interpreted source rocks for the Jumara Dome sediments are exposed in the Aravalli Craton and Nagar Parkar Massif terrain in east and northeast, and north and northwest directions, respectively (Jan, Agheem, Laghari, & Anjum, 2017). The synthesis of paleocurrent data collected for this study (n = 37, vector mean = 351.694; n = 30, vector mean = 74.995) indicates the contribution from both these terrains (Figure 8).…”
Section: Trace Elementsmentioning
confidence: 79%
“…The clastic rocks of Dhrang and Jhikadi formations posses Nb/Y ratio less than 0.7 (a feature of sub‐alkaline igneous rocks) whereas a good number of the samples of Rudramata Shales and Lodai Shales posses a high Nb/Y ratio ≥ 0.7 which points the presence of alkaline rocks in the source terranes (Table ). The alkaline rocks have been reported from the Nagarparkar Massif lying to the north and north–northwest of the Habo Dome (S. A. Ahmad, Mateen, & Chaudhry, ; Jan, Agheem, Laghari, & Anjum, ; Jan et al, ) (Figure ). These are represented by mafic dikes (hornblende microdioritc to gabbro and dolerite), some of which contain titanium augite, an indicator of alkaline affinity (Laghari et al, ).…”
Section: Source Characteristicsmentioning
confidence: 92%
“…These are represented by mafic dikes (hornblende microdioritc to gabbro and dolerite), some of which contain titanium augite, an indicator of alkaline affinity (Laghari et al, ). Other plutonic rocks of the Nagar Parkar area contain high concentration of total alkali oxides (Na 2 O + K 2 O) ranging from 8.33 wt% to 10.96 wt% (Jan et al, ) with alkaline to peralkaline character. Although trace element data on the rocks of Nagar Parkar region is not available, none of the lithocomponents of BGC contains Nb/Y ratio > 0.7 (Granite, 0.64, Tonalite–trondhjemite–granodiorite, 0.43, Mafic enclaves, 0.26, T. Ahmad et al, ) or high total alkali oxides (Na 2 O + K 2 O wt%, Granite, 7.62, Tonalite–trondhjemite–granodiorite, 7.86, Mafic enclaves, 2.19; T. Ahmad et al, ) like Nagar Parkar alkalines.…”
Section: Source Characteristicsmentioning
confidence: 99%
“…It comprises a metamorphosed basement of mafic to tonalitic rocks, Neoproterozoic granitoid intrusions in the basement, and a range of younger felsic and mafic dykes. Based on lithological and petrographic similarities with the Neoproterozoic rocks of Erinpura and Malani Igneous Suite (MIS) of the Trans Aravalli mountain belt in India, the NPIC was considered as the western extension of the MIS (Jan, Agheem, Laghari, & Anjum, ; Jan et al, ; Jan, Laghari, Agheem, & Anjum, ; Kaur, Chaudhri, Sekhar, & Yokoyama, ; Khan et al, ; Khan et al, ; Khan, Murata, Zafar, & Rehman, ; Kochhar, ; Meert, Pandit, & Kamenov, ; Muslim et al, ; Pascoe, ; Srivastava, ; Vallinayagam, ; Vallinayagam, ). Several authors have proposed that the basement rocks and the granitoids in this part of the Indian Shield were formed by an earlier Andean‐type subduction, followed by rift‐related extension tectonics in the Rodinia supercontinent (McKenzie, Houghes, Myrow, Xiao, & Sharma, ; Dharma Rao, Santosh, & Kim, ; Ashwal, Solanki, Pandit, Corfu, & Hendriks, et al, 2013; Meert et al, ; Turner, Meert, Pandit, & Kamenov, ; Jan, Laghari, Khan, Agheem, & Khan, ; Wang et al, ; Wang, Pandit, Zhao, Chen, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several other authors reported K–Ar and U–Pb zircon ages of 745 to 750 Ma from the rhyolites and granites of the MIS, Seychelles, and Madagascar islands (Ashwal et al, , ; Crawford & Compston, ; Dhar, Frei, Kramers, Nagler, & Kochhar, ; Eby & Kochhar, ; Hoshino, ; Meert et al, ; Rathore, Venkatesan, & Srivastava, ; Suwa et al, ; Torsvik et al, , ; Wang et al, ). Based on identical lithological, petrological, mineralogical and geochemical features, and age data, the granites and some of the felsic dykes in the NPIC were related to the same tectonic regime (i.e., rifting) within the Rodinia during the Neoproterozoic (Jan et al, , ; Khan et al, , , ; Rehman et al, ). Details of the individual outcrops exposed in various parts of the NPIC have been presented elsewhere (e.g., Agheem, Jan, Laghari, & Anjum, ; Jan et al, , , ; Khan et al, ; Markhand, Xia, Agheem, & Jia, ).…”
Section: Introductionmentioning
confidence: 99%